Pengaruh Kerajaan Hafsid, Ilkhanid dan Rasuliyyah di Mekah dan Implikasi Terhadap Pemerintahan Sharif Mekah Pada Era Mamluk: The Influnce of Hafsid, Ilkhanid and Rasulid in Mecca and Its Implication Towards the Sharifate of Mecca During the Mamluk Era - Mahmood, Mohamad Yusof Shah Mahmood; Mohd Nor , Mohd Roslan (Journal Al-Muqaddimah, 2024)
Mecca is the Muslim’s holiest land in the world and Ka’abah as a symbol of unity in Islam. During Mamluk’s rule, before and after them Mecca is administerd by the Sharif of Mecca among Bani Qutadah whom are legitimate descendants of Prophet Muhammad PBUH. More over beside Mamluk Mecca has become a place where some of Muslim rulling dynasties like Hafsid, Ilkhanid and Rasulid are compeating towards spreading their influences in order to gain legitimacy for their government. This research is done to find out what kind of implication from spreding their influences in Mecca towards the Sharifate government and therefore qualitative method is applied to collect historical data and analysis by descriptive. The outcome of this research found that there is an inconsistency impact of implication towards Sharifate administration based on condition dan situation which found to be positive and negative as well.